2016
DOI: 10.1007/s00464-016-5042-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety analysis of laparoscopic endoscopic cooperative surgery versus endoscopic submucosal dissection for selected gastric gastrointestinal stromal tumors: a propensity score-matched study

Abstract: LECS for selected gastric GIST patients is feasible and is associated with a better intraoperative outcome and an equal postoperative course compared with the results of ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…The management of GISTs < 2 cm is controversial; in spite of the fact that an active follow-up of the lesion could be an option, surgery should be considered because there is no data concerning growth behavior and metastasic potential[ 49 , 50 ].…”
Section: Role Of Surgeonmentioning
confidence: 99%
“…The management of GISTs < 2 cm is controversial; in spite of the fact that an active follow-up of the lesion could be an option, surgery should be considered because there is no data concerning growth behavior and metastasic potential[ 49 , 50 ].…”
Section: Role Of Surgeonmentioning
confidence: 99%
“…6 In an institution having well-experienced ESD operators, standard ESD or EMD may be a preferable treatment option for patients with G-SMT originating from Digestive Endoscopy 2018; 30 (Suppl. 1): [7][8][9][10][11][12][13][14][15][16] Endoscopic removal of gastric SMT 13 the MP layer. Moreover, several variations of ESD, such as submucosal endoscopic tumor resection (SET), submucosal tunneling endoscopic resection (STER), endoscopic submucosal tunnel dissection (ESTD), and EFTR without or with laparoscopic assistance have been successfully carried out to remove G-SMT originating from the MP layer.…”
Section: Ost G-smt Including Gist Usually Growmentioning
confidence: 99%
“…These procedures still require evidence of oncological outcomes and remain an investigational treatment . Moreover, little is known about the clinical outcomes of these ER procedures in comparison with those of LR for treating G‐SMT . Therefore, we carried out a retrospective study to compare the two resection methods, namely, ER procedures (ESD, endoscopic muscularis dissection [EMD], and EFTR) and LR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of complications after gastric GISTs resection is ∼1.8% to 22.7% 22 , 27 , 30 , 33 ; these complications mainly include pulmonary infection, gastrointestinal bleeding, anastomotic stenosis, gastro-esophageal reflux, anastomotic fistula, and delayed gastric emptying. In this study, no postoperative pulmonary infection was observed, which may be related to no placement of nasogastric tube during the perioperative period.…”
Section: Discussionmentioning
confidence: 99%